Low concentrations of Lactobacillus rhamnosus GG ( Yoba®) are safe in male Drosophila melanogaster - Keneth Iceland, Kasozi; Aisha, Bukenya; Ejike, Daniel Eze; Josephine, Kasolo; Dickson Stuart, Tayebwa; Fred, Ssempijja; Joy, Suubo; Andrew, Tamale; Isaac, Echoru; Ibrahim, Ntulume; Sarah, Kemuma Onkoba; Lisa Nkatha, Micheni; et al. (BMC Res Notes, 2019)
Objective: The purpose of the study was to generate information on the safety of probiotics, thus the study objectives were to evaluate the effects of Yoba ® on basic physiochemical properties. The study assessed male w1118 Drosophila melanogaster which were provided food supplemented with Yoba ® at 1%, 3%, 6%, and 12% on motor function, total protein, catalase activity, and hydrogen peroxide scavenging activity and lifespan. Results: Yoba® at high concentration (≥ 6%) increased locomotor activity in Drosophila melanogaster, however, total protein, catalase, and hydrogen peroxide scavenging activity were significantly higher at 1% Yoba ® compared to 3%, 6%, and 12% Yoba ®. Yoba consumed at 1% was associated with greater physiological benefits in Drosophila melanogaster. Findings in the study offer a rationale for the consumption of Yoba ® at 1% in humans as is currently being promoted by the Yoba for Life consortium, however, high concentrations of Yoba ® would disrupt physiological function as shown by this study.